Analisis Implementasi Produk Pembiyaan Murabahan di Regional Financing Operation PT. Bank Syariah Indonesia Tbk, Medan - Irani Eka Putri Pohan; Nurul Jannah (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study is to find out how the implementation of Murabahah financing products that are applied to RFO PT. BSI Tbk, Medan. The research method used is descriptive-qualitative research. Researchers collected data using interview and documentation observation methods. The results of this study indicate that the analysis of the implementation of murabahah financing products at RFO PT.BSI Tbk, Medan is in accordance with the principle of DSN MUI fatwa no.04/DSN-MUI/IV/2000 It is proven that the financing is carried out with the principle of buying and selling besides that there are also things that deviate from the teachings of Islam.